Jual Beli Kredit Tanah Perkebunan Perspektif Hukum Ekonomi Syari’ah di Kabupaten Kubu Raya - Faishal Abda’uh; Moh. Asra (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2023)
This research aims to determine the law of buying and selling credit for plantation land from the perspective of sharia economic law in Kubu Raya Regency. With a sub-focus covering the Implementation and Procedures for Buying and Selling Plantation Land Credit. This research is sharia economic law research (normative-empirical research), using a prescriptive descriptive qualitative approach. The results of this research indicate that the implementation of the sale and purchase of credit for plantation land is carried out privately without being witnessed by a land deed making official (PPAT), according to sharia economic law, the implementation of this transaction is permitted and the procedure for buying and selling credit for plantation land partially complies with the provisions in sharia economic law. However, there are several procedures that are not in accordance with sharia economic law, namely, the credit period is not clearly determined, delays in the handover of credit sale and purchase objects, and requests for rental payments by sellers to buyers for the use of plantation land which is, in essence, based on credit transactions. Plantation land that has been owned by both parties has become the right of the buyer